The role of Reg IV in colorectal cancer, as a potential therapeutic target - Hu, Yiwang; Pan, Chi; Hu, Jiyi; Zhang, Suzhan (Contemporary Oncology/Współczesna Onkologia, 2015)
Regenerating islet-derived family, member 4 (Reg IV), a member of the Reg gene family, has been reported to be overexpressed in gastrointestinal tract cancers. Reg IV overexpression in tumor cells has been associated with carcinogenesis, tissue regeneration, proliferation and resistance to apoptosis. Reg IV activates the epidermal growth factor receptor (EGFR) signaling pathway in colon cancer and increases expression of B-cell lymphoma-2 (Bcl-2) and B-cell lymphoma-extra large (Bcl-xl), which are associated with the inhibition of apoptosis, results in mitogenic signaling in colon cancer cells, increase cell proliferation, metastasis and decreased apoptosis. Reg IV treatment inhibits 5-ﬂuorouracil induced apoptosis, at least two mechanisms are involved in inhibition of apoptosis by Reg IV, including Bcl-2 and dihydropyrimidine dehydrogenase (DPD). These studies may lead to novel therapeutic strategies for cancers expressing Reg IV. Recently, one proteoglycan was confirmed to disrupt this signaling pathway to perform antitumor effect. This review summaries current knowledge of the expression and roles of Reg IV in human colorectal cancer, describes the possible signaling pathway which Reg IV activates, and discusses the relevance of Reg IV as a potential therapeutic target for cancer treatment.